Quercetin Inhibits the Progression of Atherosclerosis by Enhancing the Activity of M2 Macrophages in Wistar Rats - Ermawan, Romi; Pikir, Budi Susetyo; Mulyanto, Mulyanto (Journal of Tropical Life Science, 2026)
Quercetin, widely acknowledged as an exceptionally potent antioxidant, is known for its diverse array of bioactive properties that confer numerous health benefits. However, the specific effect of quercetin on atherosclerosis progression remains unclear and warrants further investigation. This experimental study used Wistar rats with a post-test-only control-group design. It aimed to analyze the effect of quercetin in inhibiting the progression of atherosclerosis. Twelve adult male rats were selected and used to construct an experimental model that mimics atherosclerotic plaque formation. The model was achieved by administering a high-fat diet with a caloric value of 414 kcal per 100 grams and performing an endothelial injury procedure during the second week of the study. After six weeks, the rats were divided into two groups of six: the control group continued on the high-fat diet, while the quercetin group maintained the same diet and received 10 mg/kg of quercetin via gavage. At the end of week eight, the progression of atherosclerotic plaques was evaluated by measuring the activity of M1 and M2 macrophages, as well as the carotid artery intima-media thickness and the degree of carotid arterial stenosis. Quercetin administration significantly increased the activity of M2 macrophages (p=0.002, mean difference 10.66, 95% CI 5.90 - 15.41); in contrast, no significant effect was found on the activity of M1 macrophages (p=0.562), carotid artery intima-media thickness (p=0.407), and the degree of carotid arterial stenosis (p=0.734). This study emphasizes quercetin's role in inhibiting atherosclerosis progression by enhancing the activity of M2 macrophages. Additional studies are necessary to explore various quercetin doses involving more atherosclerosis parameters.